Cutaneous Horn of the Eyelid: Anatomoclinical Implications - Claudia Florida Costea; Gabriela Dimitriu; Anca Sava; Mădălina Chihaia; Cristina Dancă; Andrei Cucu; Nicoleta Dumitrescu; Dana Turliuc (Journal of Clinical Research and Ophthalmology - Peertechz Publications, 2017)
Introduction The cutaneous horn (cornu cutaneum) is a circumscribed,conical and keratotic lesion, which can hide benign or malignant lesions [1-3]. The clinical diagnosis is established based on its appearance, the lesion being classified as solitary or multiple, straight, curved or twisted, white or yellow [4,5], most often located at the level of the skin on the patient's face [4,6,7]. While the cause leading to the formation of cutaneous horns [8] is unknown, UV radiations are believed to be the trigger of this condition [9]. Usually, the cutaneous horn occurs in people over the age of 50, in both genders [10-14]. The cutaneous horn can occur in any part of the body: the malar or frontal areas, dorsum of nose, neck, lips [3], upper eyelids [2,9,12], lower eyelid [15], external ear [3,16], scalp [3,4], upper limbs [3,11,17,18], chest [9], lower limbs [1] and penis [19].